2019
DOI: 10.1111/fme.12368
|View full text |Cite
|
Sign up to set email alerts
|

Nile tilapia (Oreochromis niloticus) invasions disrupt the functional patterns of fish community in a large subtropical river in China

Abstract: Although non‐native species can modify ecosystem function, their effects in southern China have not been investigated, despite their ecological importance. This study assessed how Nile tilapia Oreochromis niloticus (L.) invasions impact the functional patterns of fish communities in the large subtropical Pearl River by analysing the relationships between invasion and body size over a 9‐year period. The relative abundance of Nile tilapia increased significantly over time. In particular, the established Nile til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…Moreover, the sight of breeding nests belonging to this species in the Klang River confirms that this species had established a breeding population in this river. In line with the findings of this study, Shuai et al [ 64 ] reported an increase in the relative abundance of O. niloticus , which is a non-native species, in a large subtropical river in China. Therefore, the ability of this alien species to successfully breed and multiply over time is confirmed, and this further explains the result of this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the sight of breeding nests belonging to this species in the Klang River confirms that this species had established a breeding population in this river. In line with the findings of this study, Shuai et al [ 64 ] reported an increase in the relative abundance of O. niloticus , which is a non-native species, in a large subtropical river in China. Therefore, the ability of this alien species to successfully breed and multiply over time is confirmed, and this further explains the result of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to some other high-risk alien ornamental fish species recorded from pet stores in the Klang Valley, Malaysia, which had been earlier screened using the FISK v2 software [ 4 ], O. niloticus was labeled as invasive. Similarly, the high invasion risk of O. niloticus had been established in other regions too, including the Iberian Peninsula [ 65 ], South Africa [ 66 ], and China [ 64 ], where they have negatively impacted the native fish species and the environment. Consequently, the negative impacts that stem from the establishment of invasive species, such as O. niloticus, are also predicted for the water bodies that were the subject of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, which spanned 9 years in the Pearl River, native sh densities decreased with increasing tilapia density. In particular, a progressive decrease in body size, such as sh plumpness, body length, and body weight, of native shes coincided with the increasing prevalence of Nile tilapia (Shuai et al 2019), and increased competition from Nile tilapia with local native species for food resources. We found that invasive tilapia forced other shes to increasingly rely on zooplankton and aquatic insect resources in the tropical river.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling data showed that the relative densities of native prey sh decreased signi cantly over time in the invaded Dongjiang River. There has been a great deal of evidence to show that the increase of tilapia in rivers affects the CPUE of the sh community and native sh species (Gu et al 2015), including the most abundant native species mud carp (Cirrhinus molitorella), black amur bream (Megalobrama terminalis), barbel chub (Squaliobarbus curriculus) and common sawbelly (Hemiculter leucisculus) (Shuai et al 2019). The larvae of these sh are an important food source for top predators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation